2016
DOI: 10.2174/1574887110666151014141650
|View full text |Cite
|
Sign up to set email alerts
|

Early Palliative Care in Advanced Oncologic and Non-Oncologic Chronic Diseases: A Systematic Review of Literature

Abstract: Early palliative care improves the main outcomes of the assistance in patients with advanced oncologic and non-oncologic chronic diseases. The available data are probably enough to consider early palliative cares a novel standard of care in these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 0 publications
0
20
0
5
Order By: Relevance
“…Undertreatment in the intervention group and crossover/compensation in the control group were hypothesized as potential reasons for these results. The most recent reviews on EPC trials conclude that the quality of studies needs to be improved and that not all outcomes examined to date have been significantly impacted [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…Undertreatment in the intervention group and crossover/compensation in the control group were hypothesized as potential reasons for these results. The most recent reviews on EPC trials conclude that the quality of studies needs to be improved and that not all outcomes examined to date have been significantly impacted [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…Early/integrated palliative care Adults or mixed samples Setting: mixed Patient outcome: quality of life 2 SRs 38,40 Two reviews addressed quality of life but conclusions varied. One review concluded on the basis of three RCTs and one quasi-experimental study all demonstrating significant improvements in quality of life that there is robust evidence that early palliative care integrated into standard oncology care significantly improves quality of life.…”
Section: (Im In)mentioning
confidence: 99%
“…5 Further recent trials and a systematic review report that early systematic provision of palliative care by many clinicians, not just by palliative care specialists, can improve quality of life of people with cancer and other advanced life limiting conditions. [6][7][8] It can also help avoid burdensome interventions of low benefit. 9 Studies of older people in Australia and people with chronic disease in Canada showed significant reductions in hospital admissions.…”
Section: What Is the Evidence For Early Palliative Care?mentioning
confidence: 99%